BUSINESS CHANGE ADAPTATION: ENHANCING STUDENTS' ENTREPRENEURIAL ACTION THROUGH DYNAMIC ENTREPRENEURSHIP EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Jayanto, Septian Angga Dwi; Mubarokah, Rovia Titin; Magwin, Dwi Ikrar; Husnah, Eni Mabarofiatul; Narmaditya, Bagus Shandy; Wardana, Ludi Wishnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This systematic literature review article aims to identify appropriate entrepreneurship education so that students are able to act entrepreneurially in a dynamic business environment. The method used in writing systematic literature review (SLR) articles is the library research method. Bibliographic sources come from Scopus, ProQuest, and Springer Link databases. Of the 1206 articles that were identified according to the research title, researchers found 8 articles that were relevant based on the research results. The results of the analysis of 8 articles found that entrepreneurship education is very important as a road map for students for entrepreneurial action in the midst of a dynamic business environment. The roadmap includes communication skills to market products and services as well as collaboration skills in groups. This becomes the strength of students to face risks in entrepreneurial actions in the midst of a dynamic business environment